Natural Products in Mitigation of Bisphenol A Toxicity: Future Therapeutic Use - Srinivasa Rao Sirasanagandla; Isehaq Al-Huseini; Hussein Sakr; Marzie Moqadass; Srijit Das; Norsham Juliana; Izuddin Fahmy Abu (MDPI, 2024)
Indexed by WOS/Scopus/ERA